Pengaruh Keberadaan Ekosistem Gambut Terhadap Mitigasi Perubahan Iklim di Kabupaten Pelalawan - Novitra, Eko; Kurniawan, Bob (JURNAL RISET INOVASI DAERAH, 2024)
The peatland ecosystem in Pelalawan Regency, Riau Province, holds significant potential for climate change mitigation through carbon storage and sequestration. This study aims to analyze the carbon storage capacity of the peatland ecosystem, assess its contribution to reducing greenhouse gas emissions, and evaluate challenges in sustainable peatland management. The research employs a quantitative approach, including carbon content measurements at various peat depths, land cover change analysis, and carbon stock estimation based on field data and secondary sources. The results indicate that Pelalawan's peatlands have a carbon storage capacity of 2.82–2.85 GtC, with a potential carbon sequestration rate of 9–12 tons CO₂ per hectare per year under natural conditions. However, pressures from land conversion, fires, and canal construction pose risks of carbon release up to 702 tons CO₂ per hectare. Restoration through hydrological management and conservation is essential to optimize the role of peatlands as carbon sinks. This study underscores the importance of collaboration among governments, communities, and private sectors in preserving peatland ecosystems to support Indonesia’s emission reduction targets and achieve the Sustainable Development Goals (SDGs).